Multivariate Comparative Analysis of Quantity of Passengers Transported by Air in The United States and Great Britain. COVID-19 Pandemic Versus Economic Security - Mieczysław PAWLISIAK; Bartosz KOZICKI (Communications of International Proceedings, 2021)
The paper utilizes the multivariate comparative analysis of quantity of passengers transported by air in the United States and Great Britain in 2019-2020 in terms of economic security. The primary data was grouped and compiled on categorized line charts and bar charts. Constant-base dynamics indicators were used to detect the dynamics of changes taking place in the considered time intervals. For illustrative purposes, additional scales were introduced on selected charts so as to observe the regularities governing the phenomenon under consideration. The study ends with a summary and conclusions.
Keywords: Air Transport; COVID-19; Multivariate Comparative Analysis; Economic Security.